PENGARUH LAYANAN DIGITAL DAN NON DIGITAL TERHADAP KEPUASAN NASABAH (STUDI KASUS BANK SYARIAH INDONESIA) - Lia Chairunisa; Rahmayati Rahmayati (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study was to determine the effect of digital and non-digital services on customer satisfaction. To find out the influence of digital services that are developing at this time. To determine the effect of direct service on customer satisfaction. This study uses a quantitative approach. The results of the study show that there is a significant effect of digital service variables on customer satisfaction. There is a significant effect of non-digital service variables on customer satisfaction. There is an influence of digital and non-digital services on customer satisfaction at Bank Syariah Indonesia. Keywords: Digital Services, Non-Digital Services, Customer Satisfaction